Resolving troubled systemically important cross-border financial institutions: Is a new corporate organizational form required? - Christine Cumming; Robert A. Eisenbeis (Federal Reserve Bank of New York, 2010)
This paper explores the advantages of a new financial charter for large, complex, internationally active financial institutions that would address the corporate governance challenges of such organizations, including incentive problems in risk decisions and the complicated corporate and regulatory structures that impede cross-border resolutions. The charter envisions a single entity with broad powers in which the extent and timing of compensation are tied to financial results, senior managers and risk takers form a new risk-bearing stakeholder class, and a home-country-based resolution regime operates for the benefit of all creditors. The proposal is offered 1) to highlight the point that even in the face of a more efficient and effective resolution process, incentives for excessive risk taking will continue unless the costs of risk decisions are internalized by institutions, 2) to suggest another avenue for moving toward a streamlined organizational structure and single global resolution process, and 3) to complement other proposals aimed at preserving a large role for market discipline and firm incentives in a post-reform financial system.
Keywords: G20; G21; G28; G38; 330; Financial regulatory reform; corporate governance; bank charter; bank insolvency